Sistem Ekonomi Makro menurut Abu Yusuf - Musaiyana Musaiyana; Yadi Janwari; Dedah Jubaedah (STAI Al-Mas'udiyah, 2025)
Abu Yusuf's thoughts on the macroeconomic system are examined in this study. The problem raised is how Abu Yusuf provides ideas and contributions of thought in the macroeconomic system through several approaches. The methodology uses a qualitative approach that involves a descriptive-analytical analysis of Abu Yusuf's works, especially his work entitled Kitab